2010
DOI: 10.1088/0029-5515/50/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of (2,1) NTM threshold in JET advanced scenarios

Abstract: The limit to high performances advanced scenario discharges with q min above unity is generally set by the (2,1) magneto-hydro-dynamic (MHD) mode in JET. We investigate here the possibility that this mode is a (2,1) neoclassical tearing mode (NTM) by computing the critical island width at which such mode would be unstable, using a nonlinear MHD code where the relevant bootstrap current physics is accounted for. We show that the triggering of a (2,1) NTM is consistent with a lowering of the critical island widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…It can be observed that with the step adjustment rules in Section 4, the behavior of the Newton-Krylov solver is close to its optimum in both the linear and the nonlinear part of the dynamics. An extensive use of the code for production purposes also supports this observation [30].…”
Section: Application To An Ideal Internal Kinksupporting
confidence: 58%
“…It can be observed that with the step adjustment rules in Section 4, the behavior of the Newton-Krylov solver is close to its optimum in both the linear and the nonlinear part of the dynamics. An extensive use of the code for production purposes also supports this observation [30].…”
Section: Application To An Ideal Internal Kinksupporting
confidence: 58%
“…proxies of the ratio of the thermal kinetic to magnetic pressure There is also an apparent correlation of [8,[13][14][15]. Because this limit is a resistive mode rather than an ideal mode, the result is often a dramatic loss of energy confinement rather than an immediate disruption.…”
Section: Existence Domainsmentioning
confidence: 99%
“…For a q ¼ m=n island of full width w at rational surface q of poloidal mode m and toroidal mode n, the island growth or decay 4,6,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] is here given by the MRE,…”
Section: Form Of the Modified Rutherford Equation Used For Empirimentioning
confidence: 99%